2002
DOI: 10.1080/14794800008520107
|View full text |Cite
|
Sign up to set email alerts
|

Equity Issues Affecting Mathematics Learning Using Ict

Abstract: Our concern is the inequities that arise from dzferential access and use of educational technology in mathematics for groups characterised by gender, ethnicity, income level and ability. As access to information and communications technology (KT) increases both in homes and schools, our paper asks whether previous inequities are being ironed out or exacerbated. Equity is consideredj-om the three perspectives proposed by Fennema (1990) , namely in terms o$ (a) opportunities to learn (physical access); (b) educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
2
0
5
Order By: Relevance
“…Perkembangan saat ini banyak negaranegara maju dan berkembang menggunakan teknologi sebagai media pembelajaran mereka, menggunakan teknologi sebagai media pembelajaran di kelas mampu meningkatkan pemahaman sehingga siswa dapat belajar lebih efektif. Jika di dalam kelas guru menerapkan pembelajaran dengan teknologi, maka keterlibatan siswa menjadi interaktif dalam proses pembelajaran, dan pembelajaran menjadi lebih mengasyikkan dan lebih menghibur bagi siswa (Eyyam & Yaratan, 2014), (Lin, Chen, & Liu, 2017) , (Chee, Yahaya, & Ibrahim, 2017), & (Hennessy & Dunham, 2002). Media belajar dengan teknologi dapat membuat siswa menjadi interaktif dalam proses pembelajaran, maka ketika menyampaikan materi pelajaran yang sulit dipahami siswa tidak merasa bosan, mengantuk atau tidak mendengarkan penjelasan guru, sehingga siswa dapat fokus dalam proses belajar mengajar.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Perkembangan saat ini banyak negaranegara maju dan berkembang menggunakan teknologi sebagai media pembelajaran mereka, menggunakan teknologi sebagai media pembelajaran di kelas mampu meningkatkan pemahaman sehingga siswa dapat belajar lebih efektif. Jika di dalam kelas guru menerapkan pembelajaran dengan teknologi, maka keterlibatan siswa menjadi interaktif dalam proses pembelajaran, dan pembelajaran menjadi lebih mengasyikkan dan lebih menghibur bagi siswa (Eyyam & Yaratan, 2014), (Lin, Chen, & Liu, 2017) , (Chee, Yahaya, & Ibrahim, 2017), & (Hennessy & Dunham, 2002). Media belajar dengan teknologi dapat membuat siswa menjadi interaktif dalam proses pembelajaran, maka ketika menyampaikan materi pelajaran yang sulit dipahami siswa tidak merasa bosan, mengantuk atau tidak mendengarkan penjelasan guru, sehingga siswa dapat fokus dalam proses belajar mengajar.…”
Section: Pendahuluanunclassified
“…Hal ini menunjukkan bahwa siswa cenderung senang atau berminat dalam mengikuti kegiatan pembelajaran permutasi dan kombinasi menggunakan media berbasis android. Hal ini sejalan dengan pendapat yang menyatakan bahwa jika di dalam kelas guru menerapkan pembelajaran dengan teknologi, maka keterlibatan siswa menjadi interaktif dalam proses pembelajaran, dan pembelajaran menjadi lebih mengasyikkan dan lebih menghibur bagi siswa (Eyyam & Yaratan, 2014), (Hennessy & Dunham, 2002), & (Lin, Chen, Liu, 2017).…”
Section: Respon Siswa Terhadap Pembelajaranunclassified
See 1 more Smart Citation
“…The communication and representational skills through images, graphing, text students are automatically increased where ICT is properly used among school students [18]. ICT swifts up the graphing, plotting process and reflects on the relationships between data [20]. By resorting, reordering data in different ways, ICT helps in exploring problems [17].…”
Section: Why Ictmentioning
confidence: 99%
“…In their review of research linking ICT use to cognitive skills, Subrahmanyam, Kraut, Greenfield, and Gross (2000) concluded that computer use plays a salient role in cognitive development, including spatial, iconic, and particularly visual intelligence skills that are “especially useful in the fields of science and technology where proficiency in manipulating images on a screen is increasingly important” (p. 128). In a similar vein, reviewers (e.g., Hennessy & Dunham, 2002) have commented that, given relatively weak correlations often found between technology use and academic performance, the use of technology may not directly relate to academic performance, but first directly relate to key cognitive skills essential for improved learning, such as better information handling, abstract conceptualization, or divergent thinking associated with the problem-solving capacity. Indeed, Hew and Brush (2007) made a clear point that the “use of technology has the potential to provide innovative educational opportunities by reorganizing students’ cognitive processes and problem-solving activities” (p. 228).…”
Section: The Potentially Mediating Role Of Problem-solving Skillmentioning
confidence: 99%